2020
DOI: 10.1002/anie.202009002
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic Formation of High‐Entropy Alloy Nanoparticles

Abstract: High-entropy alloy (HEA) nanoparticles hold great promise as tunable catalysts. Despite the fact that alloy formation is typically difficult in oxygen-rich environments, we found that Pt-Ir-Pd-Rh-Ru nanoparticles can be synthesized under benign low-temperature solvothermal conditions. In situ X-ray scattering and transmission electron microscopy reveal the solvothermal formation mechanism of Pt-Ir-Pd-Rh-Ru nanoparticles. For the individual metal acetylacetonate precursors, formation of single metal nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 43 publications
(28 reference statements)
2
55
0
Order By: Relevance
“…S4). This is the smallest nanoparticle size for HEAs reported in the references [9,11,30,31]. This facilitates exposing more reactive sites for the electrocatalytic process due to the large specific surface area (Table S2).…”
Section: Articles Science China Materialsmentioning
confidence: 99%
“…S4). This is the smallest nanoparticle size for HEAs reported in the references [9,11,30,31]. This facilitates exposing more reactive sites for the electrocatalytic process due to the large specific surface area (Table S2).…”
Section: Articles Science China Materialsmentioning
confidence: 99%
“…Under the hydrothermal treatment at 120°C, the first molecule of acetylacetone metal salt dissociates to produce a chain autocatalytic reaction, which spontaneously forms randomly distributed M 1 OM 2 bonds (corresponding to the process of rapid nucleation to form solid nanosphere within the initial 5 min, Figure 2c). [42] Secondly, other acetylacetone groups then successively added onto M 1 OM 2 bonds which forms…”
Section: Experimental Synthesis and Characterizations Of Heosmentioning
confidence: 99%
“…Therefore, to reduce the sizes of HEAs and increase their specific surface areas, it is imperative to develop new synthetic methods for HEA preparation (Table 1). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Firstly, Yao et al reported a two-step carbon-thermal shock (CTS) method to prepare eight-element HEA nanoparticles (Figure 2a,b); since then, numerous scientists have begun to explore HEA nanoparticle synthesis methods. [46] Their research group then proceeded to apply this method to prepare HEAs using other element types.…”
Section: Size and Morphologymentioning
confidence: 99%